LINGBEE AS INTEREST DRIVEN IN BRAINSTORMING SPEAKING CLASS - Rahmatul Ummu Arifin; Ammang Latifa; Salasiah Ammade (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This Research Aims to Measure the Students’ Interest in Brainstorming Speaking Class by Using Lingbe. The Researcher Used Lingbe as The Students’ Interest Driven In Brainstorming Speaking Class. The Researcher Involves Technology in Interactive Learning. In This Case the Researcher Offers an Interactive Application Called Lingbe.A Pre-Experimental Method Was Conducted by The Researcher in This Study. The Population Was The Xii Grade Students Of Mipa Of Sman 2 Barru. Due To This Semester Consisted Six Intact Class (228 Students), The Researcher Used The Cluster Sampling Method In Deciding The Research Sample. The Instruments That Were Used In Collecting The Data Were An Informal Likert’s Scale Questionnaire And  Analysed By Using Spss Application.The Results Of The Research Showed That The Students Stated Interested In Learning English Using Lingbe Assisted By Brainstorming In Their Speaking Class. The Mean Score Of Students’ Interests Was 54.85 And Considered As Moderately Interested.